If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -1(3x + -7) = 28 Reorder the terms: 6m + -1(-7 + 3x) = 28 6m + (-7 * -1 + 3x * -1) = 28 6m + (7 + -3x) = 28 Reorder the terms: 7 + 6m + -3x = 28 Solving 7 + 6m + -3x = 28 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 6m + -7 + -3x = 28 + -7 Reorder the terms: 7 + -7 + 6m + -3x = 28 + -7 Combine like terms: 7 + -7 = 0 0 + 6m + -3x = 28 + -7 6m + -3x = 28 + -7 Combine like terms: 28 + -7 = 21 6m + -3x = 21 Add '3x' to each side of the equation. 6m + -3x + 3x = 21 + 3x Combine like terms: -3x + 3x = 0 6m + 0 = 21 + 3x 6m = 21 + 3x Divide each side by '6'. m = 3.5 + 0.5x Simplifying m = 3.5 + 0.5x
| 5(-3k-6)=-150 | | X/3-14=66 | | -4.2=-n+2.4n | | 3(5c+2p)= | | 9m-(-7)=61 | | 0.33x+0.66=0.25 | | -2y-2(4x+3)=-56 | | 3x^3+23x^2-36x=0 | | 21n^2-140n-50=-1 | | 4x+5+2x-20+57=180 | | -8(8x+1)-5(x-5)=17 | | 8t-6=7 | | 7x+3=6(c-1)+9 | | 8(2+6m)=7m+16 | | 5x+8y=-58 | | -6g-4(2g-8)=4 | | 112/-8 | | 3.4(2+6b)=18b | | 10X+45=245 | | 5x+10=2x | | -2r^3(3r^2+4)(3r^2-4)= | | 13x=35+5x | | 3p+2=-10(-p-10)+(4-4p) | | 3x+4+8x-24=108 | | 35x^2-60x+8=1-6x | | z+9=31 | | 1/2x^2-8=-5 | | 2x+1x+15=x | | 3b^2+5b+0=0 | | 2a^2+6a+9=0 | | 3+2xm=7 | | -8x+3(-8x+1)=-7x+3(1+4x) |